Physicochemical Properties and Antioxidant Activity of Three Types of Monofloral Honey from Indonesia - Sulistyianingsih; Achmad Toto Poernomo; Riesta Primaharinastiti (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2022)
Background: In addition to minerals, honey contains carbohydrates (glucose and fructose), protein, amino acids, water, enzymes, ash, vitamins, and other substances. Compounds of honey can affect the chemical properties of honey. Knowing the physicochemical properties of honey is very important because physicochemical properties affect the quality of honey. One of the biological activities of honey is an antioxidant. Antioxidants can interfere with oxidative processes, prevent disease, and play an important role in the body's defence system. Objective: to determine and compare physicochemical properties (color, viscosity, ash content, water content, reducing sugar (glucose), total phenolic compound, HMF) and antioxidant activities of monofloral honey samples from Indonesia. Methods: The color of honey are categorized using the Pfund scale. Viscosity measurement is carried out using a Brookfield viscometer. The water content is carried out using a refractometer. Phenolic content and antioxidant activities analysis were carried out by UV-VIS spectrophotometer. Results: The results show that rambutan honey from Malang has the highest physicochemical properties and antioxidant activity, which had an amber color, water content of 21.7% b/b, acidity 20.7 mL NaOH/Kg, viscosity of 33.08 poise, ash content of 0.17% b/b, reducing sugar 69.38%b/b, total phenolics content 533.7 mg GAE/Kg sample and IC50 0.111 µg/mL. Conclusion: The quality of honey varies from region to region. The best honey (according to SNI) is rambutan honey from Malang.